Pola Pendidikan Karakter Kristiani Era New Normal Pada Generasi Alfa - Jeane M. Tulung; Irene Preisilia Ilat; Yunita Kemur; Michael Fabio Polii (Pascasarjana IAKN Manado, 2022)
The study aims to identify, analyze and describe how the normal new era Christian character education pattern of the alpha generation at GMIM buloh elementary school, along with inhibitory factors and efforts to overcome inhibitory factors. The weakening of Christian character in the normal new era alpha generation reflected in the GMIM Buloh elementary school has been one of the reasons researchers elevate the heading